A Review of Strawberry Photobiology and Fruit Flavonoids in Controlled Environments - Warner, Rachael; Wu, Bo-Sen; MacPherson, Sarah; Lefsrud, Mark (Frontiers in Plant Science, 2021)
Rapid technology development in controlled environment (CE) plant production has been applied to a large variety of plants. In recent years, strawberries have become a popular fruit for CE production because of their high economic and nutritional values. With the widespread use of light-emitting diode (LED) technology in the produce industry, growers can manipulate strawberry growth and development by providing specific light spectra. Manipulating light intensity and spectral composition can modify strawberry secondary metabolism and highly impact fruit quality and antioxidant properties. While the impact of visible light on secondary metabolite profiles for other greenhouse crops is well documented, more insight into the impact of different light spectra, from ultraviolet (UV) radiation to the visible light spectrum, on strawberry plants is required. This will allow growers to maximize yield and rapidly adapt to consumer preferences. In this review, a compilation of studies investigating the effect of light properties on strawberry fruit flavonoids is provided, and a comparative analysis of how light spectra influences strawberry’s photobiology and secondary metabolism is presented. The effects of pre-harvest and post-harvest light treatments with UV radiation and visible light are considered. Future studies and implications for LED lighting configurations in strawberry fruit production for researchers and growers are discussed.